The Determinants of Commercial Banks Profitability and Importance of Remittance in Lebanese Banks: Return of Equity and Remittance in Lebanon - Ayhan, Fatih (International Journal of Contemporary Economics and Administrative Sciences, 2021)
For the developing countries, it is important to have effective functioning and developed banking sector to growth. In this study, the factors determining the banking profitability in Lebanon as a developing country were examined. The study primarily investigates the effects of remittance (REM), capital adequacy(CA) and Returns of average assets (ROA) on return on equity (ROE) in Lebanon. The annual data covers the 13 banks period between 2008 and 2019. According to results of the model estimated through the System Generalized Moments Estimator, ROA, REM, and CA variables have positive coefficient and statistically significant in explaining ROE. The findings shows that the indicators related with the banking sector are more influential for the return on equity in Lebanon rather than remittance.